Prevalence of Renal Artery Stenosis in Patients Undergoing Coronary Angiography and its predictors - Adhikari, Krishna Prasad; Malla, Rabi (Journal of National Heart and Lung Society Nepal, 2026)
Background: Renal artery stenosis (RAS) causes secondary hypertension, progressive renal insufficiency and flash pulmonary edema. This study evaluates the prevalence of renal artery stenosis in patients undergoing coronary angiography and to assess its predictors. Methods: It was a prospective observational study involving 207 patients who underwent coronary angiography and screened for the presence of renal artery stenosis in Shahid Gangalal National Heart Centre (SGNHC) from September 2014 to June 2015. Demographic, clinical, angiographic and lab parameters were statistically analyzed using SPSS 16.. Results: Among the 207 patients, 135(65.21%) were male and 72(34.78) were female. Mean age was 57.12 ±10.01 years. Among conventional risk factors, hypertension was most prevalent (58.93%) followed by hypercholesterolemia (53.43%), smoking (38.64), family history of ischemic heart disease (27.53%) and diabetes (19.81%). Coronary artery disease (CAD) was present in 54.10% (n=112) with left main disease, triple vessel disease, double vessel disease and single vessel disease in 4,22,37,49 patients respectively. RAS was present in 18.35% (n=38); thirty in patients with CAD and eight in patients without CAD. Thirty four (16.42%) patients had unilateral RAS and 17 (8.21%) patients had significant RAS defined as more than 50% stenosis. Among patients with CAD, significant RAS was associated with age > 65 years (p=0.001), hypertension (p=0.001), extent score >4 of coronary artery disease (0.037) and triple vessel disease (p=0.05). Conclusion: The prevalence of total cases of RAS in patients undergoing CAG was 18.35 % out of which 8.21% had significant RAS. The high risk subsets of RAS in patients with CAD can be predicted from coronary angiography and demographic features. Patients of advancing age, multivessel CAD, high extent score>4, hypertension and positive family history of IHD were the high risk subsets for probable RAS.